MORPHOLOGICAL VERSUS MOLECULAR CHARACTERIZATION OF THREE SIMILAR PIERID SPECIES OF BUTTERFLIES - LALHLIMPUIA PACHUAU; CATHERINE VANLARUATI; N. SENTHIL KUMAR (International Journal of Pharma and Bio Sciences, 2012)
The morphological diversity and genetic similarity of three Pierid species (both male and female) of butterflies- Pieris canidia, Pieris napi and Pieris brassicae has been studied. RAPD-PCR analysis using seven decamer primers produced discrete bands of various size revealing genetic variations as well as similarities among the three species of butterflies. Some species specific bands were obtained using primers: MA04 (750 bp), MA 13 (650 bp), MA 15 (650bp) for P. napi; MA04 (1000 bp), MA 05 (1600bp) and MA 13 (1400 bp) for P. brassicae and OPT05 (350 bp) for P. canidia. The specific bands can be considered as diagnostic bands for these species. The NTSYS-pc result of the morphological characteristics is supported by morphological similarities between the species. Maximum similarity between male and female of the species is shown in P. canidia where this species have only mild variation in their wing pattern, including coloration and distribution of spots. Therefore, the male and female of the other two species (P. napi and P. brassicae) are more different not only in the prominance of their spots but also in their colorations and spots on their wings. The results were supported by the dendrogram which showed clustering of males and females of each species. The dendrogram generated by using morphological data however, is not in congruence with RAPD data. Similarly, mitochondrial DNA variation among the three species was studied by sequencing 650 bp of the cytochrome c oxidase I gene (CO1). These sequences were then aligned with existing sequences retrieved from NCBI database confirming the genetic similarity of the three species with the same species from other regions and also the genetic dissimilarity between the different species of the same family.